( | X | + | 2 | ) | ÷ | 4 | − | ( | 2 | X | − | 3 | ) | ÷ | 6 | = | 1 | + | X |
方程左边 = | X | × | 1 4 | + | 2 | × | 1 4 | − | ( | 2 | X | − | 3 | ) | × | 1 6 |
= | X | × | 1 4 | + | 1 2 | − | ( | 2 | X | − | 3 | ) | × | 1 6 |
= | 1 4 | X | + | 1 2 | − | 2 | X | × | 1 6 | + | 3 | × | 1 6 |
= | 1 4 | X | + | 1 2 | − | 1 3 | X | + | 1 2 |
= | - | 1 12 | X | + | 1 |
- | 1 12 | X | + | 1 | = | 1 | + | X |
- | 1 12 | X | − | X | = | 1 | − | 1 |
- | 13 12 | X | = | 1 | − | 1 |
- | 13 12 | X | = | 0 |
- | 0 | = | 13 12 | X |
13 12 | X | = | - | 0 |
X | = | - | 0 | ÷ | 13 12 |
= | - | 0 | × | 12 13 |
X | = | 0 |